Professional Digital Competence Development of English Teachers in Jakarta - Kwarti, Tanti Andira; Santosa, Imam (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The aim of this study was to reveal the Professional Digital Competence (PDC) level of English teachers, particularly in Jakarta. According to The Norwegian Centre for ICT in Education 2017, there are seven PDC, namely Subject and Basic Skill, School and Society, Ethics, Pedagogy and Subject Didactics, Leadership of Learning Processes, Interaction and Communication, and Change and Development. The descriptive interpretative analysis was used to identify the PDC level of English teachers using questionnaires through Google Form. The descriptive interpretative analysis showed that most teachers have reached competence level. However, the result represented an average percentage of 27% in Ethics, 20% in Leadership of Learning Processes, 27% in Interaction and Communication, and 36% in Change and Development of teachers who have not reached competence level. This signified that these four PDC needs to be more considered and improved.